Explorasi Falsafah "Nggahi Rawi Pahu" dalam Pendidikan Islam pada Siswa Woja, Kabupaten Dompu - Abdul Malik; Nur Laelah; Ratika Ningsih (Journal of Gurutta Education, 2024)
This research aims to explore the implementation of Islamic educational values within the philosophy of "Nggahi Rawi Pahu" among students at SMAN 2 Woja, Woja District, Dompu Regency, and to examine the shift in Islamic educational values within this philosophy among the students of SMAN 2 Woja. The study adopts a qualitative approach with a narrative method, conducted at SMAN 2 Woja, Woja District, Dompu Regency. Data collection techniques include observation, interviews, and documentation, with students and Islamic Education teachers as the respondents. The findings reveal that the implementation of Islamic educational values within the philosophy of "Ngahi Rawi Pahu" is evident in the efforts of teachers to uphold and preserve Islamic values throughout the learning process, through advising the students. However, there is a shift in the philosophy of "Nggahi Rawi Pahu", where some students demonstrate a lack of discipline and ethics. Despite the teachers' efforts to provide advice, motivation, and guidance to the students, only a small portion of them adhere to it, while others do not align with the guidance provided. The implications of this study underscore the importance of paying closer attention to maintaining and preserving Islamic educational values within the context of the "Ngahi Rawi Pahu" philosophy to effectively implement them among students at SMAN 2 Woja, Dompu Regency.